FINANCIAL PERFORMANCE MEASUREMENT - PROFITABILITY OF INVESTMENT AND ADDED ECONOMIC VALUE - VĂDUVA CECILIA ELENA; VĂDUVA MARIA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2019)
Within the decentralized profit center, strategic units, the general manager has the authority to adopt a wide range of operational decisions regarding the products assembly, prices, level and type of used assets. The financial measure to assess the managerial performance and the inflation has to be represented by the obtained profit at the used assets level. The company’s managers may appreciate if the profits generate an adequate profitability of the capital invested in a unit by putting in a relation the profit of unit with the used assets. The capital may have alternative uses, the managers need to be concerned about whether the profitability of the invested capital exceeds the cost of this capital which can be measured by the profitability generated by another alternative to be used. Another reason to measure the profitability of capital is represented by the promotion of a control and analysis in the process of organizing capital budgeting. Without certain forms to measure the effective profitability of capital in controlling the budgeting process of investments, there can be a reduced stimulation for the managers to estimate the future fluxes of treasury. Measuring the efficiency of the invested capital puts managers' attention on ways to reduce the need levels, especially debts and stocks.